Disability and Mothering. Liminal Spaces of Embodied Knowledge, de Lewiecki-Wilson, C. y Cellio, J. (eds.) - Arruabarrena Ubetagoyena, Ane (Revista Española de Discapacidad, 2013)
Reseña de la obra ’Disability and Mothering. Liminal Spaces of Embodied Knowledge’ (2011) de Cynthia Lewiecki-Wilson y Jen Cellio.